Handbook of research on the applications of international transportation and logistics for world trade - Ceyhun, Gökçe Çiçek, 1980- (IGI Global, 2019)
""This book explores exploring the effective and productive solutions to global transportation and logistics by applying fundamental and in-depth knowledge together with current applications and future aspects"- Resumé vydavatel
Keywords: logistika (management); doprava; mezinárodní obchod; distribuce zboží; business logistics; transportation; international trade; distribution of goods; elektronické knihy; příručky; electronic books; handbooks and manuals